The role of ethnolinguistic identity, vitality and trust in perceived language climate change: the case of Swedish speakers in Finland - Lindell, Marina; Näsman, Marina; Nyqvist, Fredrica; Björklund, Siv; Nygård, Mikael; Hemberg, Jessica (Journal of multilingual and multicultural development, 2025)
This article explores perceived language climate in a nation-specific setting - a largely unexplored research field. It contributes to the literature on intergroup relations (specifically the relations between ethnolinguistic majority and minority groups) in terms of social identity and ethnolinguistic vitality theories. More specifically, the research focus on Swedish speakers in Finland and analyse the perceived language climate from a societal-minority perspective. Since the majority/minority proportions differ between municipalities and regions, we examined two levels: participants' own municipalities and the national level. Data originated from the national Barometer survey conducted in 2019 among Swedish speakers aged 18 and over (n = 3,804). Associations between perceived language climate and the explanatory variables were analysed using logistic regression. Overall, the analyses carried out reveals that ethnolinguistic identity, objective local vitality, access to services in one´s own mother tongue and political and social trust are closely linked and all contribute to explain a deteriorating language climate. However, different patterns were evident for the language climate at the local and national levels. The results can enhance our understanding of perceived language climate in a multilingual context.